A Philosophical Survey Of The Influence Of The Mdeia On Violence Among Youths - Ikegbu, Ephraim Ahamefula; Bisong, Peter Bisong; Maduka, Enyimba (European Scientific Journal, ESJ, 2016)
The media are like a two-edged sword; it could built, it could also destroy. It has the capacity to increase the virtue level of a society; it also has an equal capacity to increase the vices of the society. From surveys it appears to these writers that, the media at present is wielding its vicious powers more. An increase in cases of homicides, terrorism, crime, violence and other social ills in the world is a clear testimony to this assertion. Since the state or the government exists to produce virtues in the citizens, it is imperative that the government takes serious steps to curb the dysfunctional effects of the media on the citizens and the society at large. The government should not be left alone to do this, the religious leaders, physicians, psychologists, philosophers, parents and the media practitioners themselves need to contribute their quota to evolve a media of our dreams – a media that would yield positive and beneficial fruits to the society. The media should be an instrument aimed at shaping the lives of the youth and the society. As an educative, instructive, didactic and healing therapeutic facility, the negatives associated with the media should be avoided by aspiring to embrace the positive effects of their relevance.